Caregiver perspectives on TB case-finding and HIV clinical services for children diagnosed with TB in Tanzania. Issue 4 (2nd April 2020) - Emerson, Courtney; Ndakidemi, Elizabeth; Ngowi, Bernard; Medley, Amy; Ng'eno, Bernadette; Godwin, Munuo; Ntinginya, Nyanda; Carpenter, Deborah; Kohi, Wanze; Modi, Surbhi
ABSTRACT: Caregivers of children with tuberculosis (TB) and HIV play a critical role in seeking healthcare for their children. To assess the perspectives of caregivers of pediatric TB patients, we conducted 76 in-depth interviews at 10 TB clinics in 5 districts of Tanzania in March 2016. We assessed how the child received their TB diagnosis, the decision-making process around testing the child for HIV, and the process of linking the child to HIV treatment in the event of an HIV diagnosis. Caregivers suspected TB due to cases in their family, or the child being ill and not improving. Most caregivers noted delays before confirmation of a TB diagnosis and having to visit multiple facilities before a diagnosis. Once diagnosed, some caregivers reported challenges administering TB medications due to lack of pediatric formulations. Reasons for accepting HIV testing included recurrent illness and HIV symptoms, history of HIV in the family, and recommendation of the clinical provider. Caregivers described a relatively seamless process for linking their child to HIV treatment, highlighting the success of TB/HIV integration efforts. The multiple clinic visits required prior to TB diagnosis suggests the need for additional training and sensitization of healthcare workers and better TB diagnostic tools.